Objectives of assessing students’ linguistic skills through their written productions - Bensalah, Sabrine (El Omda in Linguistics and Discourse Analysis, 2025)
In a language classroom, teaching learners can only be effective if it is primarily based on errors, allowing the teacher to evaluate their teaching methods through assessment strategies. This article aims to highlight the importance of assessment conducted by foreign language teachers to measure the quality of their teaching and, most importantly, to gauge learners’ language abilities.